Classroom-Based Assessment System to Improve the Quality of Learning in Malaysia and Indonesia - Poerwanti, Jenny Indrastoeti Siti; Marmoah, Sri; Supianto, Supianto; Sukarno, Sukarno; Istiyati, Siti; Mahfud, Hasan (Mimbar Sekolah Dasar, 2023)
Malaysia and Indonesia have introduced their educational systems and are developing human resources using learning evaluation systems. Based on the issues raised, this study aims to portray the learning assessment in primary schools in Indonesia and Malaysia in accordance with the educational program utilized in both countries and the impediments experienced in carrying out classroom-based evaluation in schools. This studyused the research literature survey technique to gather information on a research topic fromnews, official government documents, etc. The analysis was conducted using a compilation of data from several references related to the assessment of primary school learning in Merdeka curricula, or other documents relevant to this study. The results of this study revelead that the assessment used in primaryschools in Indonesia refers to Minister of Education and Culture Regulation No. 21 of 2022, namely formative assessment and summative assessment. The Merdeka curriculum aimsat create a positive, high-quality learning atmosphere in Indonesia. Education system in Malaysia implements the concept of school-based assessment (SBA) in line with the implementation of Lower School Standard Curriculum, known as Primary School Curriculum. The ability to develop classroom-based assessments, the creativity of teachers in designing assessments, and knowledge literacy issues are all barriers to implementing classroom-based assessments in both countries.